2020
DOI: 10.1038/s41589-020-0621-y
|View full text |Cite
|
Sign up to set email alerts
|

Active turnover of genomic methylcytosine in pluripotent cells

Abstract: Epigenetic plasticity underpins cell potency, but the extent to which active turnover of DNA methylation contributes to such plasticity is not known and the underlying pathways are poorly understood. Here we use metabolic labelling with stable isotopes and mass spectrometry to quantitatively address the global turnover of genomic methylcytidine (mdC), hydroxymethylcytidine (hmdC) and formylcytidine (fdC) across mouse pluripotent cell states.High rates of mdC/hmdC oxidation and fdC turnover characterize a forma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 69 publications
0
32
0
Order By: Relevance
“…TET enzymes have also been shown to oxidize thymine to generate 5hmU directly, leading to 5hmU:A mismatches ( Pfaffeneder et al, 2014 ; Olinski et al, 2016 ). Protein readers of 5hmU:G and 5hmU:A also include chromatin regulators and DNA repair enzymes involved in BER ( Pfaffeneder et al, 2014 ), and the repair of 5hmU:A by long-patch BER or non-canonical mismatch repair could lead to the indirect removal of adjacent 5mC in the genome ( Metivier et al, 2008 ; Santos et al, 2013 ; Grin and Ishchenko, 2016 ; Spada et al, 2020 ). In primed embryonic murine pluripotent stems cells (PSCs) and the developing zygote, other non-oxidative and cell-cycle independent mechanisms of DNA demethylation have also been reported that may utilize deamination of mC by AID and DNA repair processes ( Santos et al, 2013 ; Amouroux et al, 2016 ; Spada et al, 2020 ), however, the majority of active DNA demethylation in mPSCs was shown to be driven by oxidation of 5mC ( Spada et al, 2020 ).…”
Section: Writers and Erasers Of Dna Methylationmentioning
confidence: 99%
“…TET enzymes have also been shown to oxidize thymine to generate 5hmU directly, leading to 5hmU:A mismatches ( Pfaffeneder et al, 2014 ; Olinski et al, 2016 ). Protein readers of 5hmU:G and 5hmU:A also include chromatin regulators and DNA repair enzymes involved in BER ( Pfaffeneder et al, 2014 ), and the repair of 5hmU:A by long-patch BER or non-canonical mismatch repair could lead to the indirect removal of adjacent 5mC in the genome ( Metivier et al, 2008 ; Santos et al, 2013 ; Grin and Ishchenko, 2016 ; Spada et al, 2020 ). In primed embryonic murine pluripotent stems cells (PSCs) and the developing zygote, other non-oxidative and cell-cycle independent mechanisms of DNA demethylation have also been reported that may utilize deamination of mC by AID and DNA repair processes ( Santos et al, 2013 ; Amouroux et al, 2016 ; Spada et al, 2020 ), however, the majority of active DNA demethylation in mPSCs was shown to be driven by oxidation of 5mC ( Spada et al, 2020 ).…”
Section: Writers and Erasers Of Dna Methylationmentioning
confidence: 99%
“…The availability of new ultra‐high performance liquid chromatography (UHPLC)‐MS 2 procedures in combination with synthetic isotope standards and reagents enable the quantification of AP and βE‐sites, [9,17] and the parallel determination of the xdC levels and BER repair events. This now allows us to gain information about the ROS induced xdC levels [18–19] . We selected as a model organism the fungus Amanita muscaria , [20] which was collected from its natural environment.…”
Section: Figurementioning
confidence: 99%
“…Our data suggest that, while some of the fdCs have a permanent or semi‐permanent character, because in mESCs even with full BER (Tdg +/+ ) the levels never drop to the ROS level, this is questionable for cadCs. Removing fdC at these (semi)permanent sites then requires Tdg‐independent pathways that were recently investigated in detail [19] …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations